2015
DOI: 10.1002/em.21987
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of DNA methylation induced by past arsenic treatment causes persistent genomic instability in mammalian cells

Abstract: The mechanisms by which arsenic-induced genomic instability is initiated and maintained are poorly understood. To investigate potential epigenetic mechanisms, in this study we evaluated global DNA methylation levels in V79 cells and human HaCaT keratinocytes at several time points during expanded growth of cell cultures following removal of arsenite exposures. We have found altered genomic methylation patterns that persisted up to 40 cell generations in HaCaT cells after the treatments were withdrawn. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 63 publications
(82 reference statements)
0
15
0
Order By: Relevance
“…Other mechanisms proposed to mediate iAs toxicity – namely changes in DNA methylation ( Huang et al, 2004 ; Hughes, 2002 ; Kile et al, 2012 ; Mauro et al, 2016 ) – were not identified by our studies in zebrafish (not shown). In fact, there is nearly no overlap in the gene expression changes induced by iAs and by mutants that have a defect in DNA methylation ( Chernyavskaya et al, 2017 ; Jacob et al, 2015 ), and our preliminary studies found neither an impact on global DNA methylation nor synergy with mutants that have DNA methylation loss (not shown).…”
Section: Discussionmentioning
confidence: 64%
“…Other mechanisms proposed to mediate iAs toxicity – namely changes in DNA methylation ( Huang et al, 2004 ; Hughes, 2002 ; Kile et al, 2012 ; Mauro et al, 2016 ) – were not identified by our studies in zebrafish (not shown). In fact, there is nearly no overlap in the gene expression changes induced by iAs and by mutants that have a defect in DNA methylation ( Chernyavskaya et al, 2017 ; Jacob et al, 2015 ), and our preliminary studies found neither an impact on global DNA methylation nor synergy with mutants that have DNA methylation loss (not shown).…”
Section: Discussionmentioning
confidence: 64%
“…DNA methylation, histone modification and microRNA expression have been identified as the prominent epigenetic mechanisms of i As toxicity . i As alteration of epigenetic mechanisms has also been linked to an up‐regulation of cancer‐related genes, as well as a down‐regulation of programmed cell death .…”
Section: Mechanisms Involved In Arsenic Tumorigenesismentioning
confidence: 99%
“…Taken together, the data of the present study provide novel in vitro and mammary tumor xenograft evidence that exposure to inorganic trivalent arsenic, such as NaAs III may increase resistance to endocrine therapy based on TAM through reduction in BRCA1 and ERα expression. Future studies with ERα-positive breast cancer patients residing in geographical regions at high risk of exposure to As III are warranted to investigate whether the dysregulation of CpG hypermethylation of BRCA1 and ESR1 causes persistent genomic instability (55), and variations in efficacy of therapies based on antagonists of the ERα. As DNA methylation changes are potentially reversible, they may offer a novel target for combination therapies of ER-positive breast tumors with epigenetic drugs.…”
Section: Discussionmentioning
confidence: 99%